MODEL PERTUMBUHAN DUA SAMPEL - Sudarno, Sudarno (MEDIA STATISTIKA, 2008)
Growth curve model is generalization of the multivariate regression models. This paper determine growth curve model at two samples of ras. They are observed body weight after given by substances. The problems will be done are testing for an outlier, testing for multivariate normality, testing for hogeneous, test of the adequacy of the model, and estimate of the parameters model. In doing computation and visualization of statistics at needed formulas, use up date some softwares, such as SAS, Minitab, MATLAB, etc. If the estimated model is known, it can be used to some objectives. The estimate model could be applied to predicted tool for next time, give characteristic and properties of the model. The growth of rat which be given thyroxin substance, at beginning time cause significant increasing of the body weight, but after at sixth weeks, given substance imply significant decreasing of their body weight, too. Meanwhile for the rat be given thyouracil, at beginning time to tenth weeks, their body weight affect slowly increasing by continue. Therefore thyroxin substance should be given before seventh weeks, but for thyouracil substance could be given continuosly if cause increasing the body weight. This result could be used to optimalization of rat growth. Â  Key words: Multivariate normal test, Adequacy of model test, Growth curve model.